The Effect of Covid-19 Pandemic on Stock Returns: An Evidence of Indonesia Stock Exchange - Mugiarni, Ajeng; Wulandari, Permata (Journal of International Conference Proceedings, 2021)
The pandemic Covid-19 caused panic not only in health sectors but also weakened the world’s economy. The stock market, as one of the barometers of the economy, was hit by the pandemic Covid-19. The impact of Covid-19 on the stock market provides a signal for investors. Stock returns are what investors look for when investing in stocks. Returns on the stock exchange respond to several events, one of which is the news about health related to the Covid-19 pandemic. This study aims to seek whether the Covid-19 outbreak affects stock returns in Indonesia Stock Exchange. Using daily data of Covid-19 confirmed case, daily data of Covid-19 death cases, and stock returns data in Indonesia from January 2, 2020, to December 31, 2020. The panel-data regression model is used to estimate the result of the study. This study shows that stock returns in Indonesia Stock Exchange respond negatively significantly as the number of confirmed cases increases also stock returns in Indonesia respond negatively significantly to the daily growth of death cases. This study also finds that stock return in consumer goods and basic chemical industry were the impacted industries caused by pandemic Covid-19. Empirical findings could be used for the practitioner to consider investing in the stock market to avoid the significant impact of such outbreaks in the future.